Pengaruh Citra Merek/Brand Image Terhadap Keputusan Pembelian Konsumen Pada Produk Eiger Palangka Raya - Tonich Uda; Rinto Alexandro; Sri Rohaetin; Junita Romasta Sormin; Fendy Hariatama (Edunomics Journal, 2022)
The purpose of this study was to determine and analyze the influence of brand image (brand image) on purchasing decisions on Eiger Palangka Raya products. In conducting this research, the quantitative method is used, while the data collection is done by analyzing the data and submitting a questionnaire to buyers or customers at the Eiger Palangka Raya store. The population in this study were consumers or buyers at the Eiger Palangka Raya store and the sample was determined using the Slovin technique formula with 99 samples. Validity test is done through the calculation of IBM SPSS Statistics 23 while the test for relativity uses the Cronbach's alpha formula. The classical assumption test uses (1) validity test (2) reliability test and (3) normality test. Data analysis techniques using (1) Simple Linear Regression Analysis (2) Hypothesis testing: F test and T test (3) Determination Coefficient Test (R Square). From the calculation results of the simple linear regression coefficient between X and Y, namely Y = 25,824 + 0.432X it can be concluded that there is a significant influence between Brand Image / Brand Image on Purchasing Decisions. Hypothesis testing results F Test shows F arithmetic (4,478)> F table (3.09) with a significance level of 0,000 <0.05 and Hypothesis Testing T Test shows that t arithmetic (3,116)> t table (1,988) with a significance level of 0,000 < 0.05. Then it can be concluded that H0 is rejected and the hypothesis accepted is H1 which means that the Brand Image variable has a significant influence on the purchase decision variable. The result of the coefficient testing determines the value of R Square of 0.378 (37.8%). This means that 37.8% of Purchasing Decisions are influenced by Brand Image, and the remaining 62.2% is influenced by other factors.